Effects of a Nurse-Led Web-Based Fall Prevention Program on Fall Risk and Fear of Falling Among Older Adults: A Randomized Controlled Trial - Nur Sema Kaynar Demirel; Selda Secginli (Healthcare, 2026)
Objectives: This study aimed to evaluate the effects of a nurse-led Web-Based Fall Prevention Program (Web-FPP) on fall risk, fear of falling, fall-preventive behaviors, and the number of falls among community-dwelling older adults aged 65 years and older. Methods: A single-blind, stratified randomized controlled trial was conducted with 72 older adults (36 intervention, 36 control) in Türkiye. The Web-FPP was delivered over six weeks and included educational content, video-based exercises, and home safety strategies accessed through a web platform. Outcomes were assessed at baseline, immediately after the intervention, and at 3-month follow-up using the Timed Up and Go test (TUG), the Falls Efficacy Scale (FES), and the Falls Behavioural (FaB) Scale. Results: Compared with the control group, the intervention group showed significantly greater improvements in TUG performance, fear of falling, and fall-preventive behaviors, and these gains were maintained at three months (p < 0.05). No significant between-group difference was observed in the number of falls during the 3-month follow-up (p > 0.05). Conclusions: The findings suggest that nurse-led web-based fall prevention programs may represent an effective community-based strategy for reducing fall risk and fear of falling among older adults. Further studies with longer follow-up are needed to determine their effects on actual fall incidence.